Cyber-criminology defense in pervasive environment: A study of cybercrimes in Malaysia - Manmeet Mahinderjit Singh; Richard Frank; Wan Mohd Nazmee Wan Zainon (Bulletin of Electrical Engineering and Informatics, 2021)
The growth of technologies; infrastructures and platforms with less or no security protection in emerging big data and internet of things (IoT) trends increase the likelihood of cybercrime attacks. With the rise of coronavirus disease-2019 (Covid-19) pandemic towards mankind, more cybercrimes are designed to penetrate one’s cognitive mind in revealing sensitive details. In this paper; an exploration of cybercrime threats in Southeast Asia country; Malaysia from year 2008 up to 2020 and its hike trends and impacts will be discussed. An investigation revolving the study of cyber-criminology and the reasoning behind the growth in terms of technological advancement will be presented. The findings suggest that the consequences and impacts of the cyberspace attacks are beyond the loss of money and reputations. It now becomes the failure of the global systemic altogether. As a mechanism to handle this would be to focus on protecting mission critical applications in pervasive environment. In this paper, a comprehensive authentication and authorization framework in safeguarding applications and users in the pervasive environment will be presented.